HUBUNGAN AKTIVITAS FISIK DAN DURASI TIDUR TERHADAP TEKANAN DARAH SISTOLIK PADA MAHASISWA KEPERAWATAN - Hanifah, Afi Wilda; Syahruramdhani, Syahruramdhani (Jurnal Lintas Keperawatan, 2025)
Physical activity and sleep duration are increasingly being recognized as crucial health-promoting lifestyle factors. However, it is disorganized among academics, such as students, these days. Less active physical activity in Yogyakarta Province increased from 20% to 25.2 percent between 2013 and 2018. If this behavior continues for an extended period, it may increase the risk of developing high systolic blood pressure. This study aims to investigate the effects of physical activity and sleep duration on systolic blood pressure in nursing students. The study method is quantitative research using a descriptive correlational design and a cross-sectional approach. Ninety-eight respondents were recruited using simple random sampling, with data collected using the IPAQ, STQ questionnaire, and blood pressure measured with a sphygmomanometer. The Spearman rank correlation is used as a statistical test. The study's findings revealed a p-value of 0.009 for the relationship between physical activity and systolic blood pressure and a p-value of 0.026 for the relationship between sleep duration and systolic blood pressure. Physical activity and sleep duration have a significant effect on systolic blood pressure in nursing students.Keyword: physical activity, sleep duration, systolic blood pressure